The Effects of the Endocannabinoids Anandamide and 2-Arachidonoylglycerol on Human Osteoblast Proliferation and Differentiation - Smith, Marie (PLoS One, 2015)
The endocannabinoid system is expressed in bone, although its role in the regulation of bone growth is controversial. Many studies have examined the effect of endocannabinoids directly on osteoclast function, but few have examined their role in human osteoblast function, which was the aim of the present study. Human osteoblasts were treated from seeding with increasing concentrations of anandamide or 2-arachidonoylglycerol for between 1 and 21 days. Cell proliferation (DNA content) and differentiation (alkaline phosphatase (ALP), collagen and osteocalcin secretion and calcium deposition) were measured. Anandamide and 2-arachidonoylglycerol significantly decreased osteoblast proliferation after 4 days, associated with a concentration-dependent increase in ALP. Inhibition of endocannabinoid degradation enzymes to increase endocannabinoid tone resulted in similar increases in ALP production. 2-arachidonoylglycerol also decreased osteocalcin secretion. After prolonged (21 day) treatment with 2-arachidonoylglycerol, there was a decrease in collagen content, but no change in calcium deposition. Anandamide did not affect collagen or osteocalcin, but reduced calcium deposition. Anandamide increased levels of phosphorylated CREB, ERK 1/2 and JNK, while 2-arachidonoylglycerol increased phosphorylated CREB and Akt. RT-PCR demonstrated the expression of CB(2) and TRPV1, but not CB(1) in HOBs. Anandamide-induced changes in HOB differentiation were CB(1) and CB(2)-independent and partially reduced by TRPV1 antagonism, and reduced by inhibition of ERK 1/2 and JNK. Our results have demonstrated a clear involvement of anandamide and 2-arachidonoylglycerol in modulating the activity of human osteoblasts, with anandamide increasing early cell differentiation and 2-AG increasing early, but decreasing late osteoblast-specific markers of differentiation.